A Study on the Reasons for Retirement: A Focus on Age as a Major Factor - Mohd Noar, Zaihan (IIUM Medical Journal Malaysia, 2018)
This study was carried out to investigate the reasons that influence individuals to plan for retirement. A survey was conducted among employees of the International Islamic University Malaysia in Kuantan. Reasons to retire are almost similar across the globe, given that the basic needs of human beings are similar. There are many studies and literatures that investigate the factors that influence retirement which relates to the socio-economic factor such as retirement age, income, and gender. De Vaney identified that age and income are the important factors that act as a guide to pre-retirees in their retirement planning process.1 In this study, attaining the retired age is the main factor that relate to the individual’s planning for retirement. Other factors include household income, family and health. The findings of this study are parallel to the other research based on the analysis of the available literature review. Several implications emerge from these empirical findings. First, employees should prepare a proper retirement planning in their life and second, the authorities should provide better care and facilities to retirees.